Comparison of clock gene expression in SCN, retina, heart, and liver of mice. - Peirson, S; Butler, J; Duffield, G; Takher, S; Sharma, P; Foster, R (2006)
In mammals, the suprachiasmatic nuclei (SCN) in the hypothalamus are the site of a central circadian pacemaker, regulating overt rhythms of behaviour and coordinating the rhythmic activity of oscillators in peripheral tissues. Circadian rhythms in all tissues appear to arise from interacting transcriptional-translational feedback loops, involving a core set of clock genes. Whilst it seems likely that there will be broadly similar mechanisms between the central and peripheral oscillators, the extent to which the fine details of gene expression are conserved between different organs has yet to be assessed. In this study, we examine the molecular profile of clock genes within the central SCN pacemaker and peripheral oscillators, identifying differences in phasing, amplitude, waveform, and basal expression levels.